Role of the TWEAK-Fn14-cIAP1-NF-κB Signaling Axis in the Regulation of Myogenesis and Muscle Homeostasis - Enwere, Emeka K.; Adam, Nadine; LaCasse, Eric C.; Korneluk, Robert G. (Frontiers in Immunology, 2014)
Mammalian skeletal muscle maintains a robust regenerative capacity throughout life, due largely to the presence of a stem cell population known as “satellite cells” in the muscle milieu. In normal conditions, these cells remain quiescent; they are activated upon injury to become myoblasts, which proliferate extensively and eventually differentiate and fuse to form new multinucleated muscle fibers. Recent findings have identified some of the factors, including the cytokine TNFα-like weak inducer of apoptosis (TWEAK), which govern these cells’ decisions to proliferate, differentiate, or fuse. In this review, we will address the functions of TWEAK, its receptor Fn14, and the associated signal transduction molecule, the cellular inhibitor of apoptosis 1 (cIAP1), in the regulation of myogenesis. TWEAK signaling can activate the canonical NF-κB signaling pathway, which promotes myoblast proliferation and inhibits myogenesis. In addition, TWEAK activates the noncanonical NF-κB pathway, which, in contrast, promotes myogenesis by increasing myoblast fusion. Both pathways are regulated by cIAP1, which is an essential component of downstream signaling mediated by TWEAK and similar cytokines. This review will focus on the seemingly contradictory roles played by TWEAK during muscle regeneration, by highlighting the interplay between the two NF-κB pathways under physiological and pathological conditions. We will also discuss how myogenesis is negatively affected by chronic conditions which affect homeostasis of the skeletal muscle environment.